Impact of renal impairment and human organic anion transporter inhibition on pharmacokinetics, safety and tolerability of relebactam combined with imipenem and cilastatin. Issue 5 (23rd January 2020) - Bhagunde, Pratik; Colon‐Gonzalez, Francheska; Liu, Yang; Wu, Jin; Xu, Shiyao Sherrie; Garrett, Graigory; Jumes, Patricia; Lasseter, Kenneth; Marbury, Thomas; Rizk, Matthew L.; Lala, Mallika; Rhee, Elizabeth G.; et al.
Abstract : Aims: Two phase 1, open‐label studies were conducted to investigate the effect of renal impairment (RI) and organic anion transporter (OAT) inhibition on pharmacokinetics (PK) and safety of relebactam (REL) plus imipenem/cilastatin (IMI). Methods: Study PN005 evaluated the PK of REL (125 mg) plus IMI (250 mg) in participants with RI vs healthy controls. Study PN019 evaluated the PK of REL (250 mg) and imipenem (500 mg; dosed as IMI) with/without probenecid (1 g; OAT inhibitor) in healthy adults. Results: Geometric mean ratios (RI/healthy matched controls) of area under the concentration–time curve from time 0 to infinity (AUC0‐∞ ; 90% confidence interval) for REL, imipenem and cilastatin increased as RI increased from mild (1.6 [1.1, 2.4], 1.4 [1.1, 1.8] and 1.6 [1.0, 2.5], respectively) to severe (4.9 [3.4, 7.0], 2.5 [1.9, 3.3] and 5.6 [3.6, 8.6], respectively). For all 3 analytes, plasma and renal clearance decreased and corresponding plasma apparent terminal half‐life increased with increasing RI. Geometric mean ratios ([probenecid+IMI/REL]/[IMI/REL]) of plasma exposure for REL and imipenem were 1.24 (1.19, 1.28) and 1.16 (1.13, 1.20), respectively. The dose fraction excreted (fe) in the urine decreased progressively from mild to severe RI. Probenecid reduced renal clearance of REL and imipenem by 25 and 31%, respectively. Compared with IMI/REL, coadministration of IMI/REL with probenecid yielded lower fe for REL and imipenem. In both studies, treatment was well tolerated; there were no serious adverse events or discontinuations due to adverse events. Conclusion: RI increased plasma exposure and similarly decreased clearance of REL, imipenem and cilastatin; IMI/REL dose adjustment (fixed‐ratio) will be required for patients with RI. Probenecid had no clinically meaningful impact on the PK of REL or imipenem.